2000
DOI: 10.1290/1071-2690(2000)036<0167:eoesoa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF ELECTRICAL STIMULATION ON Β-Adrenergic RECEPTOR POPULATION AND CYCLIC AMP PRODUCTION IN CHICKEN AND RAT SKELETAL MUSCLE CELL CULTURES

Abstract: Expression of the beta-adrenergic receptor (betaAR) and its coupling to cyclic AMP (cAMP) synthesis are important components of the signaling system that controls muscle atrophy and hypertrophy, and the goal of this study was to determine if electrical stimulation in a pattern simulating slow muscle contraction would alter the betaAR response in primary cultures of avian and mammalian skeletal muscle cells. Specifically, chicken skeletal muscle cells and rat skeletal muscle cells that had been grown for 7 d in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…During this process, CGRP increases voltage-gated SR Ca 2 þ release within hours, resulting from a quantitatively similar increase in releasable SR Ca 2 þ content (Avila et al, 2007). When chicken and rat skeletal muscle cells were cultured for 7 days and were then subjected to electrical stimulation for additional 2 days, the ability of these cells to synthesize cAMP was increased by almost two-fold (Young et al, 2000). In our study, electrical stimulation of differentiated C2C12 myotubes may have caused upregulation of cAMP biosynthesis; in this case, H 3 receptor activation may inhibit cAMP elevation and prevent overcontraction.…”
Section: Discussionsupporting
confidence: 50%
“…During this process, CGRP increases voltage-gated SR Ca 2 þ release within hours, resulting from a quantitatively similar increase in releasable SR Ca 2 þ content (Avila et al, 2007). When chicken and rat skeletal muscle cells were cultured for 7 days and were then subjected to electrical stimulation for additional 2 days, the ability of these cells to synthesize cAMP was increased by almost two-fold (Young et al, 2000). In our study, electrical stimulation of differentiated C2C12 myotubes may have caused upregulation of cAMP biosynthesis; in this case, H 3 receptor activation may inhibit cAMP elevation and prevent overcontraction.…”
Section: Discussionsupporting
confidence: 50%
“…These results support the view that the in vivo hypertrophic effect of clenbuterol and cimaterol on skeletal muscle in both birds and mammals is due, at least in part, to a reduction in protein breakdown, probably mediated by 2 -adrenoceptors. -Adrenoceptors, predominantly of the 2 -subtype, have been identified in quail primary myotubes (Young et al, 2000) and in rat skeletal muscle (Jensen et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of exogenous electrical currents and electric fields, and their influence on various cell plasma membrane receptors, has been well documented [17], [22], [23]. By activating these cell receptors, biochemical events within the cell cytoplasm and nucleoplasm can be influenced through a number of plasma membrane interactions and in different cellular signaling pathways.…”
Section: B Cellular-molecular Biology Standpointmentioning
confidence: 99%
“…Young et al and Cheng et al reported that endogenous and exogenous electrical stimulation supports production and release of the nucleoside/nucleotide derived family of molecules including adenosine triphosphate (ATP) and cyclic adenosine monophosphate (cyclic AMP); along with promoting protein synthesis, amino acid transport and cellular Ca ++ influx [22], [24]. ATP is known to act as a neurotransmitter in the retina.…”
Section: B Cellular-molecular Biology Standpointmentioning
confidence: 99%